Effects of Silver – Copper (Core-Shell) Nanoparticles as Antiparasitic Drug In Some Blood Parameters of Mice - Alaa Adnan Aljanabi; A. M. Al-mussawi; Abbas Matrood Bashi (Institute of Medico-legal Publications Pvt Ltd, 2021)
The current study included the synthesis and diagnosis of the silver-copper nanoparticles Ag-Cu NPs in theform of (core-shell) , with the commercial drug Albendazole Alb loaded on it Ag-Cu NPs /Alb . Then toknow its effect on some hematological parameters of the orally dosed mice at three concentrations (400, 800and 1200) mg/kg. The results showed a variation in the effect according to the concentrations used comparedwith the commercial drug treatment and the control treatment using only distilled water .